ANALISIS PENGARUH KEBIJAKAN MINIMAL UANG MUKA KREDIT (DOWN PAYMENT) TERHADAP VOLUME PENJUALAN SEPEDA MOTOR DI KABUPATEN JOMBANG - WIBISONO, WAHYU (Jurnal Akuntansi AKUNESA, 2013)
This research aims to examine effect of the minimum down payment loanpolicy to sales volume of motorcycles in district Jombang. Testing functionalrelationship between two variables using simple regression statistical analysis andusing SPSS v19 software. Regression analysis using the percentage amount of creditadvances as independent variables and motorcycle sales volume as dependentvariable. Through calculation of T test, t count equal 5,2619 and 2,570582 for the ttable, so t count (5,2619)> t table (2,570582) = Ho is rejected , Ha received. So thatthe amount of credit advances significantly influence volume of sales of motorcycles.Keywords: credit advances, the policy, sales volume, effect.